Cutting their cloth: the Scottish Premonstratensians, c. 1150 to c. 1350 - Oram, Richard (Places of worship in Britain and Ireland, 1150-1350, 2018)
Keywords: 🇬🇧 great britain (general)

The Premonstratensian Canons - Smith, David M. (The Heads of Religious Houses: England and Wales, III. 1377–1540, 2008)
All the houses were abbeys except where specifically stated otherwise.ALNWICK (Northumberland), St Mary f. 1147 x 1148Lists in Colvin, pp. 392–3; A. M. Oliver in Proc. Soc. Ant. Newcastle, 3rd ser., IX (1919–20), 42–4; Heads, I, 192; Heads, II, 491.Walter de Hepscott (Hepescotes) Occ. 15 Aug. 1376 (Ch. Alnwick, p. 43).John Frechevyl Occ. 1379 (TNA, E179/62/4, m. Id).William (de) Rok (Rokk') Occ. 6 Feb. 1395 (DCM, Reg. II, f. 315v); Trin. 1404 (called Kok), Hil. 1407 (Dendy, Arch. Aeliana, 3rd ser., 6 (1910), 67–8); 10 Apr. 1407 (Nbld and Durham Deeds, p. 156).John Occ. [1415] (TNA, E101/214/5B, m. 21).John Cudberde 1419– Can. of Alnwick, pres. of abb.-el. for bl., no reason being given for the vacancy 12 May 1419 (Reg. Langley, V, p. 115, no. 1414). Probably to be identified with the abb. John who occ. from 20 June 1421 (ibid., V, p. 153, no. 1478) to 8 March 1435 (ibid., IV, p. 152, no. 1144).William Marschal (Marschall) 1437– Can. of Alnwick, pres. of abb.-el. for bl., no reason being given for the vacancy 25 May 1437 (ibid., V, p. 34, no. 1293); commn to bl. 4 July 1437 (ibid., p. 35, no. 1294). He was previously vicar of Chatton (ibid., p. 36, no. 1295). Is he the same as William below?
Keywords: 🇬🇧 great britain (general)

A la recherche d'un environnement accueillant: les Prémontrés dans les circaries d'Écosse, d'Angleterre, de Flandre et de Brabant - Appelmans, Janick (Actes officiels des 26e et 27e colloques du Centre d'Etudes et de Recherches Prémontrées, Saint-Brieuc - Abbaye de Beauport, 2000 [et] Arras -Prémontré, 2001, 2002)
Keywords: 🇧🇪 belgium (general); 🇬🇧 great britain (general)

The Provincial and General Chapters of the English Premonstratensians and their Acta, 1459-1504 - Gribbin, Joseph A. ("Stand up to godwards" : essays in mystical and monastic theology in honour of the reverend John Clark on his sixty-fifth birthday, 2002)
Keywords: ⚖️ chapters and statutes; 🇬🇧 great britain (general)

The Premonstratensian Canons - Smith, David M.; London, Vera C. M. (The Heads of Religious Houses: England and Wales, II. 1216–1377, 2001)
Keywords: 🇬🇧 great britain (general)

The Premonstratensian Order in Late Medieval England - Gribbin, Joseph A. (Boydell Press, 2000)
Keywords: 🇬🇧 great britain (general)